BRINGING LOCAL FOLKLORE TO LIFE IN THE DIGITAL ERA - Yogi Prayudi; Suherli Suherli (Adisam Publisher, 2025)
The reading interest and ability to comprehend narrative texts among elementary school students in Indonesia are still relatively low. One strategic effort that can be done is through the use of local folklore as teaching materials packaged in the form of digital media. This study aims to develop and implement teaching materials on the folklore of the Saung Galah Kingdom in the form of educational videos through the YouTube platform, and measure its effectiveness in improving the reading comprehension skills of fifth-grade elementary school students. The research method used is a descriptive qualitative with a case study approach, which involves learning observations, interviews, reading comprehension tests, and documentation. The results show that the use of local-based folklore videos can increase students' enthusiasm for learning and provide significant improvements in the aspect of reading comprehension, especially in understanding the plot, characters, and moral values in the story. In addition, this media also contributes to the preservation of local culture and strengthens students' identity with their regional cultural heritage. These findings indicate that a digital approach based on local culture is a relevant and effective strategy to address literacy challenges in the digital era.